Design and synthesis of certain mesoionic sydnonyl styrylketones as potential nonsteroidal antiinflammatory agents - Deshpande, Shreenivas Ramachandrarao; Pai, Karkala Vasantakumar; Pai, Ranganath Sridhar (Arzneimittelforschung, 2011)
In an attempt to develop effective and safer analgesic anti-inflammatory agents, nine compounds belonging to 4-[1-oxo-3-(substituted aryl)-2-propenyl]-3-(4-methoxyphenyl) sydnones, containing the structural features of mesoionic sydnone and styrylketone, have been designed and synthesized by condensing 4-acetyl-3-(4-methoxyphenyl)sydnone with various substituted aryl aldehydes and characterized by spectral studies. They have been tested for analgesic activity by acetic acid induced writhing in mice and for anti-inflammatory activity by carrageenan induced rat paw edema at 100 mg/kg body weight p.o. The compounds containing furyl and chloro substituents showed highly significant analgesic effect, while those with dimethylamino, chloro and nitro substituents exhibited highly significant anti-inflammatory effect at the end of 3 h. The compounds that showed good analgesic and anti-inflammatory activities were evaluated for ulcerogenicity in rats to assess their gastric side effects at 100 mg/kg body weight p.o. They were found to be less ulcerogenic than the standard drug.
Keywords: Analgesic effect; Anti-inflammatory effect; Mesoionic compounds; 3-(4-Methoxyphenyl)sydnone; Styrylketone; Ulcerogenicity